Soluble Polymers with Intrinsic Porosity for Flue Gas Purification and Natural Gas Upgrading. Issue 10 (23rd January 2017) - Wang, Xinbo; Liu, Yang; Ma, Xiaohua; Das, Swapan K.; Ostwal, Mayur; Gadwal, Ikhlas; Yao, Kexin; Dong, Xinglong; Han, Yu; Pinnau, Ingo; Huang, Kuo‐Wei; Lai, Zhiping
Abstract : A soluble polymer with intrinsic microporosity, 2, 4‐diamino‐1, 3, 5‐triazine‐functionalized organic polymer, is used for the first time as a solid adsorbent, providing an easy solution to overcome the fouling issue. Promising adsorption performances including good CO2 adsorption capacity, excellent CO2 /N2 and CO2 /CH4 selectivities, high chemical and thermal stabilities, and easiness of preparation and regeneration are shown.